How do we know if 'Smart Money' is really smart? Market reactions when biotechnology firms disclose the identities of investors. (8th February 2010) - Janney, Jay J.
Private placements of equity are generally viewed as signals because of the observable confidence 'smart investors' have to have in order to make the investment. We therefore ask the question if it is the transaction that creates the signal, or if it is knowledge of the investor that matters. Knowing investor identity permits others to assess the skill the investor has in assessing the value of the biotechnology firm. We examine 685 private placements and find disclosed investors have a much higher market reaction than do undisclosed investors.